(3eUGHjM GdeZGfi aj MQha GdeYGfis - (3LeGd GdOjf eMeO Hf Ydj Hf YHO Gddg GdehRYj Gdjefj, GHf fhQ GdOjfs ((3GdUOjb YeQ TeGN s)
(3ChdgG (B:s
(3CeG HYO aEfi CMeO Gddg GdcQje MeOkG jQJVjg dLdGdg s
(3BNQgG (B:s
(3heJi cGfJ ddJfHjg SbWJ GdCda GdJi ai aYd GdCeQ cbhd Pi GdQeI (B: (3CdG jG Sdei jG OGQ ei Ydi GdHdG hdG RGd efgdkG HLRYGFc GdbWQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3cJHJ HQSe GdbGVi Yaja GdOjf YHO Gddg Hf eMeO Hf CHj HcQs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GddZIs